The impact of age at first calving on first lactation performance of dairy heifers within the United Kingdom - Sherwin, Virginia Elizabeth (2017)
The objective of this research was to evaluate the performance and survival of first lactation heifers within a large sample of herds across United Kingdom and specifically to assess the association between age at first calving (AFC) on their survival. Data from 437 herds were re-structured for analysis. Descriptive statistics were calculated, and multilevel logistic regression models were used to explore factors associated with the risk of first lactation culling, fertility performance and milk production. The mean within-herd culling rate for the primiparous heifers was 15.9%. The mean within-herd AFC was 29.6 months, with 35.9% of heifers having an AFC >30 months of age. Multivariable analysis revealed a negative association between survival rate of primiparous heifers and increasing AFC, and also associations with herd culling rate in older cows and calving season. This study highlights the importance of AFC for survival of primiparous heifers, as well as the need to address heifer wastage in herds with high culling rates. The fertility performance analysis, as measured by 100 day and 200 day in calf rates, showed a negative association between being in calf by 100 days and 200 days in milk and increasing AFC. The production performance however showed a positive association between 305 day yield and increasing AFC, however the clinical relevance of this was debatable.